Pengaruh Kecerdasaan Emosional, Adversity Quotient, terhadap Minat Young Entrepreneur melalui Self Efficacy (Business and Accounting Education Journal, 2022)
The purpose of this study was to analyze the effect of emotional intelligence, adversity quotient, on the interest in becoming a young entrepreneur through self-efficacy. The population in this study were 268 students of S1 Economics Education in 2017 and the sample was taken using the Slovin formula so that 160 students were obtained. Methods of data collection by using a questionnaire. The data analysis technique used descriptive statistical analysis techniques, path analysis, partial test (t test), Sobel test, and partial determination coefficient (r2). The results showed that emotional intelligence had an effect on the interest in becoming a young entrepreneur (8.35%). Emotional intelligence has an effect on self-efficacy (6.35%). Adversity quotient affects the interest in becoming a young entrepreneur (8.58%). Adversity quotient has an effect on self efficacy (12.96%). Self efficacy affects the interest in becoming a young entrepreneur (16%). Emotional intelligence affects the interest in becoming a young entrepreneur mediated by self-efficacy. Adversity quotient affects the interest in becoming a young entrepreneur mediated by self-efficacy.